How to Solve It : modern Heuristics - Michalewicz, Zbigniew, 1952-; Fogel, David B. (Berlin Springer, 2004)
No pleasure lasts long unless there is variety in it. Publilius Syrus, Moral Sayings We've been very fortunate to receive fantastic feedback from our readers during the last four years, since the first edition of How to Solve It: Modern Heuristics was published in 1999. It's heartening to know that so many people appreciated the book and, even more importantly, were using the book to help them solve their problems. One professor, who published a review of the book, said that his students had given the best course reviews he'd seen in 15 years when using our text.
Keywords: Heurística; Algoritmos; Resolución de problemas; Programación dinámica